The Effect of Educational Qualifications and Teacher Professional Education Program on the Digital Literacy Skills of Early Childhood Educators - Anisa, Nur; Robbaniyah, Inayatur; Sutama, I Wayan; Astuti, Wuri (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Digital literacy is mastered by Early Childhood Education (ECE) teachers because the first education obtained by early childhood will be the foundation and basis of child development in the future. This study aims to determine whether there is an interaction between academic qualifications and teacher professional education on digital literacy. This research is quantitative research with a survey type. The study was conducted in Malang City, with data distributed through a questionnaire (G-Form). The data collected was analyzed with Two Way Anova with the help of the SPSS 26.0 application. Based on the research findings, it is known that there are differences in digital literacy skills based on the academic qualifications of Early Chilhood Education teachers (H1 accepted), there are differences in digital literacy skills based on the participation of Early Chilhood Education teachers in the Teacher Professional Education program (H2 accepted), and there is an interaction between academic qualifications and teacher professional education on digital literacy of Early Chilhood Education teachers (H3 accept). Skill development programs need to be held by schools to improve teacher competence.